Fault-Tolerant Protocol for Hybrid Task-Parallel Message-Passing Applications - Martsinkevich, Tatiana; Subasi, Omer; Unsal, Osman; Cappello, Franck; Labarta, Jesus (Proceedings / IEEE International Conference on Cluster Computing, 2015)
We present a fault-tolerant protocol for task-parallel message-passing applications to mitigate transient errors. The protocol requires the restart only of the task that experienced the error and transparently handles any MPI calls inside the task. The protocol is implemented in Nanos -- a dataflow runtime for task-based OmpSs programming model -- and the PMPI profiling layer to fully support hybrid OmpSs+MPI applications. In our experiments we demonstrate that our fault-tolerant solution has a reasonable overhead, with a maximum observed overhead of 4.5%. We also show that fine-grained parallelization is important for hiding the overheads related to the protocol as well as the recovery of tasks.